A Review of the Ecosystem Services Provided by the Native Oyster (Ostrea edulis): Implications for Restoration. Issue 1 (1st July 2022) - Thomas, S; Collins, K; Hauton, C; Jensen, A
Abstract: Native oyster ( Ostrea edulis ) habitat has been decimated across the majority of its natural range as a result of human activity. In recent decades, oyster restoration projects have gathered increasing support due to their potential to provide ecosystem services that offset increasing pressure from human development, resource demand, and also climate change. These ecosystem services are reviewed here, so as to inform the potential benefit of restoration projects. Ecosystem services can be divided into four categories: provisioning services through direct utilisation of oysters and the species they support, regulating services that help maintain a healthy environment, habitat services that benefit biodiversity, and cultural services that can influence tourism and wider cultural values. Ecosystem services are often interlinked in complex networks, though these can be linked back to two overarching ecosystem functions, stemming from either the filter feeding activity of oysters, or the physical reef structure that they provide. The MARINEFF oyster enhancement reefs installed in the Solent, September 2020, are intended to support the extensive Solent Oyster Restoration Project initiated by the Blue Marine Foundation. The expectation is that they will facilitate both oyster settlement and the release of larvae for the repopulation of the Solent system. This may contribute to the recovery of ecosystem services mentioned in this review. It is important to note however that there is a lack of baseline data for native oysters, and the ecosystem service values they provide are poorly constrained, meaning that ecosystem service estimates are derived largely from other species of oyster. This inhibits our ability to accurately calculate and model natural capital provided by native oysters, highlighting the necessity for further research so as to inform management and restoration targets.